Efeito da simulação de perda óssea e contenção inter-dental na deformação do tecido de suporte: análise por extensometria - Soares, Priscilla Barbosa Ferreira (2008)
Controversy exists concerning the influence of bone loss and of the dental splinting over strain of dental support tissue. The aim of this study was to analyze the effect of support bone loss and the dental splinting type on strain of the anterior mandibular bone in different regions, in simulation of the polystyrene resin mandibular model. Eighty intact human mandibular teeth (20 central incisors, 20 lateral incisors, 20 canines and 20 first premolars; being half of right side and half of left side) were selected and randomly divided in 10 groups. For strain gauge test, 10 mandibular replicas were made in polystyrene resin. Four strain gauges were fixed on 2 mandibular surfaces: buccal surface and lingual surface; and 2 regions: central incisor region and lateral incisor region. On all specimens (n=10) were tested 7 experimental situations: Cont, control group, without bone support alterations and no splinting; Po, simulating 5mm of bone loss between canines teeth; PoRc, Po condition associated with splinting made between canines teeth with composite resin only; PoFa, Po condition and splinting with 0.25mm wire ligature only; PoFaRc, Po condition with splinting made with association between wire ligature and composite resin; PoFvRcExt, Po condition with extra-coronal splinting made with association between fiber glass and composite resin; PoFvRcExt, Po condition with intracoronal splinting made with association between fiber glass and composite resin. The strain values were assessed under compressive oblique load until 150N applied over anterior teeth in a universal testing machine. The data obtained for 50N, 100N and 150N were individually analyzed with 3-way ANOVA followed by the Scheffe test (=.05). Statistical analysis showed that the strain on buccal surface was always higher than on lingual surface, and the strain measured on incisor central region was always higher than on incisor lateral region. The simulation of bone loss resulted in significant increase on strain for 100N and 150N loads. The dental splinting types that use adhesive system and composite resin resulted in significant decrease on strain measured in all sites, with values similar to Cont levels. Within the limitations of this study, it was observed that the loss of dental support increase the strain values mainly in buccal region. The dental splinting made with composite resin produced significantly decrease on strain measured on dental support irrespective of load intensity tested.